A sensitive and high-throughput fluorescent method for determination of oxidase activities in human, bovine, goat and camel milk. (30th January 2021) - Zou, Zhengzheng; Bouchereau-De Pury, Claire; Hewavitharana, Amitha K.; Al-Shehri, Saad S.; Duley, John A.; Cowley, David M.; Koorts, Pieter; Shaw, Paul N.; Bansal, Nidhi
Abstract: Milk oxidases are an integral part of milk immune system, and good indicators for milk thermal history. Current assay methods for milk oxidases are either insensitive, tedious or not cost-effective. In this study, a high-throughput fluorescence assay method for determination of xanthine oxidase (XO) and polyamine oxidase (PAO) activities in milk samples was developed. The hydrogen peroxide generated by XO catalysed oxidation of hypoxanthine, and PAO catalysed oxidation of spermine, was coupled to horseradish peroxidase conversion of Amplex® Red (1-(3, 7-dihydroxyphenoxazin-10-yl)ethanone) to the fluorescent product resorufin. The assay was highly sensitive, with limits of detection of activity in milk being 3 × 10 −7 and 7 × 10 −7  U/mL for XO and PAO, respectively. Intra-run and inter-run results showed good assay repeatability and reproducibility. The assay was successfully applied to survey the XO and PAO activities in human, bovine, goat and camel milk samples, and it can be readily adapted for measurements of other oxidase activities.